American evangelicals in Egypt : missionary encounters in an age of empire - Sharkey, Heather J. (Heather Jane), 1967- (Jews, Christians, and Muslims from the ancient to the modern world., 2008)
"Heather Sharkey uses Arabic and English sources to shed light on the many facets of missionary encounters with Egyptians. These occurred through institutions, such as schools and hospitals, and through literacy programs and rural development projects that anticipated later efforts of NGOs. To Egyptian Muslims and Coptic Christians, missionaries presented new models for civic participation and for women's roles in collective worship and community life. At the same time, missionary efforts to convert Muslims and reform Copts stimulated new forms of Egyptian social activism and prompted nationalists to enact laws restricting missionary activities. Faced by Islamic strictures and customs regarding apostasy and conversion, and by expectations regarding the proper structure of Christian-Muslim relations, missionaries in Egypt set off debates about religious liberty that reverberate even today. Ultimately, the missionary experience in Egypt led to reconsiderations of mission policy and evangelism in ways that had long-term repercussions for the culture of American Protestantism."--Jacket